Exploring Podcast Learning Design: A Study of Theory, Philosophy, and Evaluation in Thesis Proposal Learning in Science Education - Dasrieny Pratiwi; Friska Octavia Rosa; Arif Rahman Aththibby (Postgraduate, University of Mataram, 2025)
Advances in digital technology, particularly the use of podcasts, open significant opportunities for innovation in learning design. This study explores podcast-based learning in the context of teaching thesis proposals for science education students, reviewed from theoretical, philosophical, and evaluative perspectives. Using a literature review and descriptive analysis, various models of podcast-based design were examined with attention to pedagogical and technological dimensions. The findings show that this approach is grounded in constructivist, cognitive, and connectivism learning theories. Philosophically, it reflects progressivism and social constructivism, emphasizing experiential learning, independence, and collaboration. Evaluation results highlight the potential of podcasts to strengthen cognitive abilities, including conceptual and analytical understanding, as well as 21st-century skills such as critical thinking, communication, creativity, and collaboration. The study concludes that podcast development in higher education must align with instructional design principles tailored to student needs and course characteristics. Further research is needed to develop flexible models and assess their long-term impact on students’ academic performance. Importantly, the outcomes provide practical implications for integrating podcasts into science education curricula and for creating evaluation systems that measure higher-order learning outcomes.